2022
DOI: 10.1002/smll.202202071
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Synergistic Electronic Interaction between Pt‐Skin Wrapped Intermetallic PtCo Nanoparticles and Co‐N‐C Support for Efficient ORR/EOR Electrocatalysis in a Direct Ethanol Fuel Cell

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.202202071. The development of low-Pt catalysts with high activity and durability is critical for fuel cells. Here, Pt-skin wrapped sub-5 nm PtCo intermetallic nanoparticles are successfully mounted on single atom Co-N-C support by exploiting the barrier effect of Co-anchor. According to a collaborative experimental and computational investigation, the increased oxygen reduction reaction activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The binding energy ( E b ) and the interlayer distance (DIS) between nanoparticles and Co–N–C carriers are calculated and presented in Figure c, corresponding to Pt/Co–N–C ( E b = 0.86 eV; DIS = 2.44 Å) and PtCo/Co–N–C ( E b = 1.76 eV; DIS = 2.04 Å). It is well illustrated in the previous literature that the higher binding energy and the smaller interlayer distance unveil the stronger interaction between nanoparticles and supports. , Thus, the above results demonstrate that the interaction between nanoparticles and supports is enhanced after forming PtCo intermetallic nanoparticles carried on Co–N–C, hence weakening the migration and aggregation of PtCo nanoparticles and increasing the stability of PtCo/Co–N–C. Besides, stronger interaction and shorter interlayer distance also facilitate charge transfer and H 2 O 2 migration from Co–N x sites to PtCo, improving the synergistic effect and accelerating the ORR kinetic rate .…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The binding energy ( E b ) and the interlayer distance (DIS) between nanoparticles and Co–N–C carriers are calculated and presented in Figure c, corresponding to Pt/Co–N–C ( E b = 0.86 eV; DIS = 2.44 Å) and PtCo/Co–N–C ( E b = 1.76 eV; DIS = 2.04 Å). It is well illustrated in the previous literature that the higher binding energy and the smaller interlayer distance unveil the stronger interaction between nanoparticles and supports. , Thus, the above results demonstrate that the interaction between nanoparticles and supports is enhanced after forming PtCo intermetallic nanoparticles carried on Co–N–C, hence weakening the migration and aggregation of PtCo nanoparticles and increasing the stability of PtCo/Co–N–C. Besides, stronger interaction and shorter interlayer distance also facilitate charge transfer and H 2 O 2 migration from Co–N x sites to PtCo, improving the synergistic effect and accelerating the ORR kinetic rate .…”
Section: Resultssupporting
confidence: 72%
“…There is a similar phenomenon when Pt is loaded on other M–N–C carriers. , Nevertheless, their activity and stability are still not satisfied with the demands for PEMFCs, which is attributed to the slight electron modulation on Pt nanoparticles from M–N–C supports and the dissolution of Pt during operation, respectively. It has been confirmed that Pt-based intermetallic catalysts possessed higher ORR activity and durability due to orderliness, compressive strain, and ligand effects in previous studies. ,,, After alloying, the electronic structure of Pt was effectively regulated and the d-band center was changed significantly, which are conducive to enhancing the inherent activity of Pt-based catalysts. Based on this, developing a catalyst through combining the ordered intermetallic compounds with M–N–C supports could achieve a significant enhancement for ORR and PEMFCs . However, Pt-alloy intermetallic compounds prepared by traditional methods showed a large particle size (around 5–10 nm), ,, which would reduce the Pt utilization and increase the oxygen mass transport resistance .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, Bu et al 60 reported that the synergistic interaction between the N-doped graphene and perovskite makes it a versatile electrocatalyst. Qiu and co-workers 61 reported the synergistic interaction between Pt-skin-wrapped intermetallic PtCo nanoparticles and Co−N−C support boosts the ORR/EOR performances in direct ethanol fuel cells. Therefore, the synergistic interaction between the CN x support and NiO x could boost the activity of the catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 99%